Color of Beer, Honey and Chilled Vodka (Petra Hanakova - Kevin B. Johnson (eds.), Visegrad Cinema. Points of Contact from the New Waves to the Present) - Blazejovsky, Jaromir (Iluminace, 2011)
Review of the collection Visegrad Cinema: Points of Contact from the New Waves to the Present.
Keywords: film literature; film theory; history of cinema